2013
DOI: 10.1093/annonc/mdt156
|View full text |Cite
|
Sign up to set email alerts
|

Estimated risk of cardiovascular disease and secondary cancers with modern highly conformal radiotherapy for early-stage mediastinal Hodgkin lymphoma

Abstract: In early-stage, mediastinal HL modern radiotherapy provides superior results compared with MF. However, there is no single best radiotherapy technique for HL-the decision should be made at the individual patient level.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
73
0
4

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 127 publications
(78 citation statements)
references
References 24 publications
1
73
0
4
Order By: Relevance
“…Our PBS plan employed a single anterior field for each patient, while anterior-posterior opposed PBS fields were used in other studies [4,17]. As ML targets usually are anterior and tend to be shallow, posterior PBS fields may unnecessarily increase heart dose.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Our PBS plan employed a single anterior field for each patient, while anterior-posterior opposed PBS fields were used in other studies [4,17]. As ML targets usually are anterior and tend to be shallow, posterior PBS fields may unnecessarily increase heart dose.…”
Section: Discussionmentioning
confidence: 99%
“…1.8 Gy(RBE)/fx. The PBS plan employed a single anterior field for each patient, which was in contrast to opposed PBS fields modeled in other studies [4,17]. The treatment planning system (TPS) Eclipse 11.0 (Varian Medical System) was used.…”
Section: Treatment Planningmentioning
confidence: 99%
See 1 more Smart Citation
“…For breast cancer, it has been shown that smaller radiation volumes than mantle field are associated with substantially lower risk, 9,26,28 which is important in view of the smaller field sizes currently used in HL treatment. 9,37 Furthermore, alkylating chemotherapy and pelvic radiotherapy appear to reduce the risk of radiotherapy-associated breast cancer, due to the high frequency of premature menopause after chemotherapy. 9,26,28,32,33 A long vs short duration of intact ovarian function after radiation was a strong predictor of subsequent breast cancer risk.…”
Section: Introductionmentioning
confidence: 99%
“…The risk of radiotherapy-related CVD after HL is expected to decrease significantly over time, because fewer patients receive combined modality treatment and radiotherapy policies have changed. 37,59 If radiotherapy is applied, the target volumes are smaller, 3-dimensional conformal radiotherapy planning is used, and the applied dose is lower. 37 Additional advanced techniques such as deepinspiration breath-hold and intensity modulated RT with butterfly techniques further significantly reduce doses to the heart and cardiac substructures.…”
mentioning
confidence: 99%